Comparison of Twisting Angle-Torsional Moment in Unstrengthened Reinforced Concrete Beams with Reinforced Concrete Beams Strengthened with CFRP Sheets - Shokri, Mojtaba; Edalati, Mahmod (Journal of History Culture and Art Research, 2017)
One of the most important strengths of concrete structures is their torsional strength in different loads. This strengthening could have a significant impact on increasing tolerability of structure relative to lateral and vertical loads and vibrations. In order to withstand the additional loads, reinforced polymers (FRP) are used today. The present study investigated the effect of using polymer composite sheets CFRP on the torsional strength and ultimate deformation of beam. Research method is practical and in this study, four types of beams with different dimensions are used to examine the effect of different loads on the torsional strength.